### 5 Answers

- RobertLv 67 years agoBest Answer
r - 2s = 14 Solve for s:

Subtract r off both sides:

-2s = 14 - r

Multiply both sides by -1 to avoid trouble later:

2s = r - 14

Divide by 2:

s = (r - 14)/2

- BeaLv 57 years ago
r - 2s = 14 First, subtract r from both sides

r - (r) - 2s = 14 - (r)

- 2s = 14 - r Now, divide both sides by -2

-2s / (-2) = (14 - r) / (-2)

s = (14 - r) / (-2)

s = (r - 14) / 2 or

s = r/2 - 7

- LuisLv 67 years ago
Dear Greg G,

r-2s=14

Since r does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting r from both sides.

-2s=-r+14

Divide each term in the equation by -2.

-(2s)/(-2)=-(r)/(-2)+(14)/(-2)

Simplify the left-hand side of the equation by canceling the common factors.

s=-(r)/(-2)+(14)/(-2)

Simplify the right-hand side of the equation by simplifying each term.

s=(r)/(2)-7

=================

Who am I, ldiazmdiaz, learn more...

http://www.youtube.com/results?search_query=kc9byk...

=================

Thanks for the interesting question!

and You're welcome

Source(s): Precalculus Solved! - ranjankarLv 77 years ago
r - 2s = 14

ADD 2s BOTH SIDES

r - 2s +2s = 14 + 2s

r = 14 + 2s

SUBTRACT 14 FROM BOTH SIDES

r - 14 = 14 + 2s -14

r - 14 = 2s

DIVIDE BOTH SIDES BY 2

( r - 14) / 2 = 2s /2 = s

ANSWER s = ( r-14) / 2

- How do you think about the answers? You can sign in to vote the answer.